2008
DOI: 10.1037/a0013178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eating disorders and disordered eating behaviors among male collegiate athletes.

Abstract: Male athletes have been hypothesized to be at increased risk for disordered eating attitudes and behaviors due to unique pressures in the sport environment. In this study, 203 male collegiate athletes from three universities completed the Questionnaire for Eating Disorder Diagnosis (QEDD; Mintz, O'Halloran, Mulholland, & Schneider, 1997) as well as provided information on binge eating and pathogenic weight control behaviors. None were classified with a clinical eating disorder, though almost 20% reported a suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
5
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 43 publications
(76 reference statements)
6
79
5
2
Order By: Relevance
“…According to a meta-analysis of studies including male athletes [4], the difference between male athletes and male controls is greater than the difference between female athletes and female controls. Various studies have found controversial results related to ED among male athletes and controls (e.g., [9,10]). …”
Section: Introductionmentioning
confidence: 99%
“…According to a meta-analysis of studies including male athletes [4], the difference between male athletes and male controls is greater than the difference between female athletes and female controls. Various studies have found controversial results related to ED among male athletes and controls (e.g., [9,10]). …”
Section: Introductionmentioning
confidence: 99%
“…We used an established protocol (e.g., Morrison et al, 2003) to qualitatively ask participants why they wanted to be muscular in order to better understand beliefs about and desire for muscularity among female student-athletes, female college students, and male student-athletes. Based on the unique need for athletes to be muscular in order to perform in sport (e.g., Petrie et al, 2008), the study's fourth hypothesis was that female student-athletes would be more likely to report functionality (i.e., sport performance) as their highest-cited reason for being muscular, in comparison to female students. Finally, in order to further determine differences between groups on reasons for being muscular, the study's fifth hypothesis was that female college students would report more reasons related to the codes within the category of external gratification (e.g., to look good, for sex appeal; see Appendix A for the study's codebook) than female student-athletes and male student-athletes.…”
Section: Current Studymentioning
confidence: 99%
“…Different sports have differential standards of muscularity requirements, which influence body image and contribute to negative outcomes. For example, performance outcome is directly related to weight and muscularity in sports where athletes must make specific weight limits to compete (e.g., wrestling); in sports where the aesthetic of the athlete's body is a strong component of performance outcome (e.g., diving); and in sports where a low body weight is thought to offer a performance advantage (e.g., cross-country; Petrie et al, 2008). Additionally, participants in contact sports (e.g., football, rugby) require a greater degree of muscularity to not only facilitate performance, but also to minimize the risk of injury (Baker & Newton, 2004;Matthews & Wagner, 2008).…”
Section: Muscularity In American Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps some men have an inflated view of women's WCR perceptions (i.e., assume that women make extremely positive inferences about men with lower WCRs) and this is one significant cause of their unhealthy approaches to diet, exercise, and/or other body modification (e.g., liposuction). Moreover, understanding male body-related attractiveness is especially important because men are more likely to attempt to alter their bodies, as opposed to their faces, to become more attractive in both healthy and unhealthy ways (e.g., Locker, Heesacker, & Baker, 2012;Petrie, Greenlead, Reel, & Carter, 2008;Steinfeldt, Gilchrist, Halterman, Gomory, & Steinfeldt, 2011). In addition, it may be useful to test more directly for influences that may impose these standards on both men and women (e.g., mass media; Tiggemann, 2005) to gain a better understanding of how these may affect the predictions generated by our model.…”
Section: Discussionmentioning
confidence: 99%